(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Empowerment in the context of women’sdevelopment is a way of defining, challenging and overcoming barriers inawoman’s life through which she increases her ability to shape her life andenvironment. It is an active, multidimensional process, which should enable womento realize their full identity and power in all spheres of life. Indiaenvisions a future in which Indian women are independent and self-reliant. Itis unfortunate that because of centuries of inertia, ignorance andconservatism, the actual and potential role of women in the society has beenignored, preventing them from making their rightful contribution to socialprogress. Entrepreneurship development and income generating activities are afeasible solution for empowering women. It generates income and also providesflexible working hours according to the needs of homemakers. Economicindependence is the need of the hour. Participation in income generatingactivities helps in the overall empowerment of women this paper focuses andprovides an insight into the challenges and advantages faced by them. Empowerment in the context of women’s development is a way of defining,challenging and overcoming barriers in a woman’s life through which sheincreases her ability to shape her life and environment. It is an active,multidimensional process, which should enable women to realize their fullidentity and power in all spheres of life. India envisions a future in whichIndian women are independent and self-reliant. It is unfortunate that becauseof centuries of inertia, ignorance and conservatism, the actual and potentialrole of women in the society has been ignored, preventing them from makingtheir rightful contribution to social progress. It is also because of distortedand/or partial information about their contribution to family and society thatthey are denied their rightful status and access to developmental resources andservices contributing to their marginalization.